SELECTION OF BACTERIAL FLORA IN THE CHLORTETARACYCLINE TREATED OIL SARDINE ( SARDINELLA LONGICEPS), INDIAN MACKEREL (RASTRELLIGER KANAGURTA) AND PRAWN (METAPENAEUS DOBSONI) DURING ICE STORAGE - SURENDRAN, P K; GOPAKUMAR, K (Fishery Technology, 2017)
The native flora of oil sardine and mackerel consisting of Pseudomonas spp; Moraxella spp; Acinetobacter spp. and Vibrio spp. underwent significant changes during ice storage. At the time of spoilage, Pseudomonas spp. were predominant. CTC treatment significantly reduced the Pseudomonas spp. in the initial stages of storage; but later Pseudomonas spp. reasserted and constituted the bulk of the spoilage flora. In prawn, the native flora was comprised of Pseudomonas spp; Acinetobacter spp; Moraxella spp. and Vibrio spp. At the time of spoilage a heterogeneous flora, consisting of Pseudomonas spp; Moraxella spp. and Acinetobacter spp. predominated. CTC treatment significantly changed the flora of prawns. During spoilage, Pseudomonas predominated in CTC treated prawns.